2017
DOI: 10.1039/c7ra01171g
|View full text |Cite
|
Sign up to set email alerts
|

Study on the structural design and performance of novel braid-reinforced and thermostable poly(m-phenylene isophthalamide) hollow fiber membranes

Abstract: Novel braid-reinforced (BR) and thermostable poly(m-phenylene isophthalamide) (PMIA) hollow fiber membranes comprising reinforced braids and a separation layer were prepared by a dry-wet spinning process for the first time. The effects of PMIA concentration and the braid composition on the structure and performance of the BR PMIA hollow fiber membranes were investigated. Field emission scanning electron microscopy (FESEM) was used to observe the morphologies of the BR PMIA hollow fiber membranes. An increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
(37 reference statements)
1
35
0
Order By: Relevance
“…The burst pressure of the pipe structure can also be approximately estimated according to Barlow’s equation 29 , 30 , as shown below: where, P represents the burst pressure, x represents the wall thickness, T is the maximum tensile stress and F s is the safety factor (typically, F s = 1). Other membrane characterizations such as field emission scanning electron microscope (FESEM), physical and mechanical properties were presented in the Supplementary Information .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The burst pressure of the pipe structure can also be approximately estimated according to Barlow’s equation 29 , 30 , as shown below: where, P represents the burst pressure, x represents the wall thickness, T is the maximum tensile stress and F s is the safety factor (typically, F s = 1). Other membrane characterizations such as field emission scanning electron microscope (FESEM), physical and mechanical properties were presented in the Supplementary Information .…”
Section: Methodsmentioning
confidence: 99%
“…To improve the mechanical strength and the crush or burst pressure of hollow fiber membranes, numerous strategies were followed (1) adding woven 24 , carbon nanotubes 25 , and inorganic salts 26 , 27 ; (2) adopting dual-layer extrusion technology 28 , 29 ; (3) employing the braid reinforced elements 30 32 . However, to the best of our knowledge, the aforementioned hollow fiber membranes are not ideal or suitable for OARO because they are mechanically weak (e.g., having a burst pressure less than 35 bar).…”
Section: Introductionmentioning
confidence: 99%
“…These groups lead to creating strong electronegativity and superior hydrophilicity PMIA membranes. These properties are the main goal to improve the antifouling property [28].…”
Section: Type Of Polymer In a Dope Solutionmentioning
confidence: 99%
“…The thin separation layer of the BHFM also contributed to the water flux enhancement because of lower thickness compared to self-support HFMs [24]. Chen et al [28] reported that the flux of braid PMIA-BHFMs was higher than the PMIA-HFMs. It is due to the PMIA-BHFMs containing an inner layer with a relatively porous structure that leads to a reduction in membrane resistance for water transfer.…”
Section: Introductionmentioning
confidence: 99%
“…When reinforced, HF fiber membranes can withstand hydraulic pressures typical for reverse osmosis (~12.5 MPa) . To our knowledge, there have been five reports (one conference paper, two patents, and two journal articles) on reinforced HF thin‐film composite (TFC) membranes and seven studies on reinforced HF UF membranes …”
Section: Introductionmentioning
confidence: 99%